Synthetic sticky bone grafts enhance bone regeneration: a preclinical evaluation in rat models - Lei LI; Haojie LIN; Siyu JIN; Shuchang HU; Wei SUN; Wei JI (Journal of Applied Oral Science)
Abstract Objectives Deproteinized bovine bone minerals (DBBMs) are effective for bone regeneration. However, their limited plasticity can hinder extensive bone defects treatment. This study aimed to develop a composite bone grafting material that is easy to deploy surgically and promotes robust bone regeneration. Methodology DBBM particles were mixed with a clinical-grade gelatin-based hemostatic gel (w/v ratio of 2/3) to create a composite material referred to as synthetic sticky bone (SSB). Structural properties were assessed using confocal laser scanning microscopy and scanning electron microscopy. To evaluate bone regenerative capacity, 20 male Sprague Dawley rats (eight to ten weeks old) with critical-size jawbone defects were treated with SSB, DBBM, or gelatin gel alone, with an empty defect as a control. Samples were collected at two and four weeks for microcomputed tomography (μCT) analysis of bone volume/total tissue volume (BV/TV), trabecular thickness (Tb. Th), trabecular number (Tb. N), and trabecular separation (Tb. Sp). Histological analyses were conducted to examine material remnants and bone formation. Results SSB showed a binary paste-like composite property with enhanced injectability and plasticity. μCT and histological assessments confirmed that the SSB-treated group had significantly greater new bone formation compared to the DBBM-treated group after four weeks. Conclusions SSB, which is a paste-like composite of DBBM particles, and a clinical-grade gelatin-based hemostatic gel demonstrated improved structural plasticity and enhanced bone regeneration, offering a promising solution for treating extensive irregular bone defects.